Heritage Stone 7. Pohorje Granodiorite: One of the Most Significant Slovenian Natural Stones - Kramar, Sabina; Trajanova, Mirka; Dolenec, Matej; Gutman, Maja; Bedjanič, Mojca; Mladenovič, Ana (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2016)
Granodiorite from the Pohorje Mountains (northeastern Slovenia) is considered the highest quality natural stone in Slovenia. Pohorje granodiorite is a grey, calc-alkaline igneous rock of Miocene age (18.7 Ma) that is distinguished by thick white aplite−pegmatite veins. It mainly consists of plagioclase, quartz, and K-feldspar, subsidiary biotite and a small amount of hornblende. It is characterized by high density, low water absorption, and low porosity, so that it exhibits high frost and salt resistance, as well as a high compressive strength and a very high flexural strength. It is widely recognized throughout the country for its durability and decorative white veins, and is the most frequently used natural stone in Slovenia today. It is mainly used as paving and cladding material for residential buildings, churches, and other structures, as well as in public areas, where it adds special character to many of the larger towns and cities. Several important buildings, some of which have been declared cultural monuments of national importance, are also decorated with this stone, including the Slovenian Parliament, the Republic Square business complex, and the Faculty of Law of the University of Ljubljana, all of which are located in Ljubljana. Since 1940, Pohorje granodiorite has also been widely used by sculptors in various monuments and fountains.